Investigating the Compatibility of Various Components in Marine Low-Sulfur Fuel Oil by Molecular Dynamics Simulations - Daping Zhou; Haijun Wei; Shuye Xue; Ye Qiu; Shen Wu; Haijie Yu (Journal of Chemistry, 2021)
Asphaltene aggregation and precipitation are one of the major issues for marine low-sulfur fuel oil used on board. Many research studies have been carried out to investigate the aggregation behavior of asphaltene under different conditions, but the mechanism of asphaltene aggregation in low-sulfur fuel oil at the molecular level is still unclear. In this work, molecular dynamics (MD) simulations were performed to calculate the solubility parameters, intermolecular interaction energies, and radial distribution function (RDF) curves of each component in marine low-sulfur fuel oil to examine their mutual compatibility. Simulation results indicate that the solubility parameter of resin gains the highest value and it is close to asphaltene. The solubility parameters of aromatic, hexadecane, and saturate decrease successively. The interaction energy between resin and asphaltene molecules is higher than that between the same kind of molecules, which means that resin can inhibit the aggregation of asphaltene molecules. Typically, a light distillate component (hexadecane) is added to heavy fuel oil to yield low-sulfur oil, and our calculations reveal that this has a negative effect on asphaltene aggregation. Specifically, asphaltene is more likely to self-aggregate, as shown by the increase in peak height in the radial distribution function of the asphaltene-asphaltene pair. The findings of this study will provide theoretical support for the production of marine low-sulfur fuel.